Vitamin E Enhances Cancer Immunotherapy by Reinvigorating Dendritic Cells via Targeting Checkpoint SHP1 - Yuan, Xiangliang; Duan, Yimin; Xiao, Yi; Sun, Kai; Qi, Yutao; Zhang, Yuan; Ahmed, Zamal; Moiani, Davide; Yao, Jun; Li, Hongzhong; Zhang, Lin; Yuzhalin, Arseniy E.; et al. (Cancer discovery, 2022)
Despite the popular use of dietary supplements during conventional cancer treatments, their impacts on the efficacies of prevalent immunotherapies, including immune-checkpoint therapy (ICT), are unknown. Surprisingly, our analyses of electronic health records revealed that ICT-treated patients with cancer who took vitamin E (VitE) had significantly improved survival. In mouse models, VitE increased ICT antitumor efficacy, which depended on dendritic cells (DC). VitE entered DCs via the SCARB1 receptor and restored tumor-associated DC functionality by directly binding to and inhibiting protein tyrosine phosphatase SHP1, a DC-intrinsic checkpoint. SHP1 inhibition, genetically or by VitE treatment, enhanced tumor antigen cross-presentation by DCs and DC-derived extracellular vesicles (DC-EV), triggering systemic antigen-specific T-cell antitumor immunity. Combining VitE with DC-recruiting cancer vaccines or immunogenic chemotherapies greatly boosted ICT efficacy in animals. Therefore, combining VitE supplement or SHP1-inhibited DCs/DC-EVs with DC-enrichment therapies could substantially augment T-cell antitumor immunity and enhance the efficacy of cancer immunotherapies. The impacts of nutritional supplements on responses to immunotherapies remain unexplored. Our study revealed that dietary vitamin E binds to and inhibits DC checkpoint SHP1 to increase antigen presentation, prime antitumor T-cell immunity, and enhance immunotherapy efficacy. VitE-treated or SHP1-silenced DCs/DC-EVs could be developed as potent immunotherapies. This article is highlighted in the In This Issue feature, p. 1599.